In Vivo Antiplasmodial and Analgesic Effect of Crude Ethanol Extract of Piper guineense Leaf Extract in Albino Mice - Kabiru, A. Y. (Scientifica (Cairo), 2016)
Antiplasmodial and analgesic effects of crude ethanol extract of Piper guineense was investigated in mice. The antiplasmodial and analgesic efficacy of the extract was judged on its ability to reduce parasitemia and writhing, respectively, in mice. The antiplasmodial screening involved treating infected mice with 200, 400, and 600 mg/kg body weight of extract while the positive control group was given standard artesunate drug. The analgesic test was carried out by administering 1000, 1500, and 2000 mg/kg body weight of extract to three groups of healthy mice, respectively, after induction of pain with 0.75% acetic acid. The positive control group was given aspirin drug. Parasitemia was reduced by 28.36%, 43.28%, and 62.69% in a dose-dependent pattern in the curative test which was significantly different (P < 0.05) from 96.03% of the standard drug. The reduction of writhing by mice given the extract was also dose-dependent (36.29, 45.43, and 59.07%). Aspirin drug was however more effective (86.36%). The extract was safe at 2000 mg/kg body weight. Phytochemical screening revealed the presence of flavonoids, tannins, phlobatannins, terpenoids, and coumarins. Result obtained in this study demonstrated the efficacy of ethanol extract of Piper guineense as an antiplasmodial and analgesic agent.